Pastiching as Artistic Research: Ifigenia/Ipermestra (Brussels, 2006) - Forment, Bruno 1978- (Genève Zenodo, 2021)
On 6 December 2006, students of the Royal Conservatoire of Brussels performed two one-act pasticci arranged by the author of this article: Ifigenia and Ipermestra. Assembled by the author of this article as experiments in the young discipline of artistic research in music, both ‘cut & paste’ operas offered opportunities to explore issues of music-dramatic syntax in opera seria. In the article, I explain how individual arias and recitatives were combined into two meta-compositions that sometimes respected, and sometimes overrode the eighteenth-century generic conventions. By revisiting the scores, libretti, archives and first-hand memories pertaining to this venture, I show that ‘pastiching’ (pasticciare) is more than a historical form; it is a transhistorical method, involving a broad network of agencies, operators, and stakeholders whose strategies can be artistic and non-artistic, convergent and divergent. Pastiching does not necessarily result in ‘works’, fixed in time and space, but rather produces meta-compositional assemblages, the transience and formal instability of which provide opportunities to showcase neglected repertoire and tackle outdated musical ontologies.
This is the open data set accompanying the homonymous article in 'Musicology Today', and consisting of two full scores and an Italian libretto with Dutch translation.
FRIS
Keywords: Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Opera seria; Pasticcio; Artistic research